Guava borer worm (Lepidoptera: Cossidae), a limiting pest in guava: biology, lifecycle and management alternatives. Issue 2 (February 2019) - Pulido Blanco, Víctor Camilo; Insuasty Burbano, Orlando Ildefonso; Sarmiento-Naizaque, Zaida Xiomara; Durán, Julio Ramírez
Abstract: In 2006, a new limiting pest in guava was reported in the provincia de Vélez, Santander, Colombia, known as the borer worm. There is no knowledge of the biology of this pest so far. The aim of this study, conducted between May 2013 and December 2014, was to establish the taxonomy, lifecycle, damage (distribution, incidence, and severity), and control alternatives of this new limiting pest in guava, as input for an integrated management program. Results showed that this pest corresponds to Simplicivalva ampliophilobia (Davis et al., 2008). The life cycle in the field lasts 330–360 days, with one generation per year (univoltine): egg, 15–30 days; larva, 270 days; prepupa, 15 days; pupa, 30 days; adult, 15–30 days. Under laboratory conditions the lifecycle lasts 259–266 days, unknown egg state duration; larva, 7–8 instars, 210 days; pupa, 42 days; imago, 7–14 days ( n = 60, α = 5%, 25.4 °C ± 4.93 °C, 55.6% ± 11.58% RH, photoperiod 0: 24). The incidence was 94% in 124 silvopastoral system farms with 7.51 ± 1.69 infested trees compared to 40.74 ± 5.52 observed trees ( n = 4, 970). The technified system showed a reduction in the average incidence of 50.83% compared to the silvopastoral guava cropping system. Severity was moderate ( n = 48) in both systems. Morphometric descriptions of eggs, larvae, pupae, and imagos were performed. Damage and associated symptoms occur when larvae remove the conducting tissues of the plant adjacent to the medulla. Crop technification combined with the use of the parasitoid Apanteles sp., and the fungi Metarhizium anisopliae and Lecanicillium lecanii represent an alternative control for this pest.